2016
DOI: 10.1007/s11751-016-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral valgus osteotomy: bone healing time in single plane and biplanar technique

Abstract: Varus deformity can be localized in the tibia, in the femur or in both. If varus deformity is localized within the femur, it is mandatory to correct it in the femur. This report presents the technique and results of a consecutive case series of lateral uniplanar and biplanar closed-wedge valgus osteotomy of the distal femur for the treatment of varus deformity of the knee. Retrospectively, fifteen patients (sixteen knees) were identified. Indications for surgery varied from unloading an osteoarthritic medial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 33 publications
2
38
0
2
Order By: Relevance
“…Referring to those reports, the clinical results of our oHTO patients are within the upper range. Only the study by van der Woude et al investigated the postoperative clinical outcome after a cDFO so far and reported a Lysholm score of 73 points and a pain level of 3 (VAS) [6]. In comparison, the patients in our cDFO group showed a 17-point higher Lysholm score and a 2-point lower postoperative pain level.…”
Section: Clinical Outcomementioning
confidence: 58%
See 3 more Smart Citations
“…Referring to those reports, the clinical results of our oHTO patients are within the upper range. Only the study by van der Woude et al investigated the postoperative clinical outcome after a cDFO so far and reported a Lysholm score of 73 points and a pain level of 3 (VAS) [6]. In comparison, the patients in our cDFO group showed a 17-point higher Lysholm score and a 2-point lower postoperative pain level.…”
Section: Clinical Outcomementioning
confidence: 58%
“…In our study, 64% (7 of 11) of the patients were within the ±3°limit of deviation with regards to preoperative planning. This is explained by the technically demanding closed wedge osteotomy, since the surgeon must rely on the accuracy of the bone resection, and intraoperative readjustment is only possible to a limited extent [6,12]. Lateral inaccuracy of DFO could be produced by the same reason and due to the tension of the gastrocnemius muscle on the distal femur.…”
Section: Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…According to the preoperative deformity analysis mentioned above, 8° of LCWDFO was performed. The surgical procedure for LCWDFO was based on the report by van der Woude et al 15. After making a 15 cm straight skin incision on the lateral aspect of the thigh, the iliotibial band was split.…”
Section: Treatmentmentioning
confidence: 99%